Preparatory Examination in Civil Procedure Law: Strategies for Swift and Efficient Justice - Hidayat, Imam; Abdul Rachmad Budiono; Budi Santoso; Rachmi Sulistyarini (Indonesia Law Reform Journal, 2024)
The rigidity of formal requirements in civil litigation in Indonesia has resulted in numerous cases being dismissed as "Gugatan Tidak Diterima" (Not Admissible), leading to a prolonged and wasteful judicial process. Many litigants spend considerable time and resources waiting, only to receive a verdict that denies access to substantive justice due to technicalities, undermining the principle of a speedy trial. Failure to meet formal requirements leads to many cases being dismissed as "Gugatan Tidak Diterima" (Not Admissible). With numerous cases being dismissed as such, a situation arises where the principle of a speedy trial is not upheld. This research focuses on the implementation of the principle of a speedy trial in terms of the judge's authority to examine formal requirements in civil procedural law. Based on the above background, three problem formulations are developed: (1) What is the essence of the preliminary examination applied in civil procedural law?  (2) What are the formal requirements of a civil lawsuit as a manifestation of the principle of a speedy trial? This article employs a normative juridical research method with legislative, conceptual, and historical approaches. Legal materials used include primary, secondary, and tertiary legal materials, which will be analyzed using grammatical, systematic, historical, futuristic, and theological interpretation techniques. Based on the above problem formulations, the author concludes that the main purpose of implementing pre-trial examination of formal requirements in Indonesia's civil legal system is to address the issue of high case volumes leading to many courts rejecting lawsuits. This delay in justice stems from rigid court processes and outdated procedures. Pre-trial examination helps minimize rejections and make the legal system more efficient. Therefore, clear rules are needed to ensure this examination is part of civil law procedures, either through Supreme Court regulations or legislation. Abstrak ekakuan persyaratan formal dalam litigasi perdata di Indonesia telah menyebabkan banyak kasus ditolak dengan putusan "Gugatan Tidak Diterima", yang mengakibatkan proses peradilan yang berkepanjangan dan sia-sia. Banyak pihak yang menghabiskan waktu dan sumber daya yang signifikan hanya untuk menerima putusan yang menolak akses terhadap keadilan substansial karena alasan teknis, yang pada akhirnya merusak asas peradilan cepat. Kegagalan untuk memenuhi persyaratan formal menyebabkan banyak kasus ditolak karena “Tidak Dapat Diterima”. Dengan banyaknya kasus yang dibatalkan, timbul situasi di mana prinsip persidangan yang cepat tidak ditegakkan. Penelitian ini berfokus pada penerapan asas speedy trial dalam kaitannya dengan kewenangan hakim untuk memeriksa syarat formil dalam hukum acara perdata. Berdasarkan latar belakang di atas, maka dikembangkan tiga rumusan masalah: (1) Apa hakikat pemeriksaan pendahuluan yang diterapkan dalam hukum acara perdata?  (2) Apa saja syarat formal gugatan perdata sebagai perwujudan asas speedy trial? artikel ini menggunakan metode penelitian yuridis normatif dengan pendekatan legislasi, konseptual, dan historis. Bahan hukum yang digunakan meliputi bahan hukum primer, sekunder, dan tersier, yang akan dianalisis dengan menggunakan teknik penafsiran gramatikal, sistematis, historis, futuristik, dan teologis. Berdasarkan rumusan masalah di atas, penulis menyimpulkan bahwa tujuan utama dilaksanakannya pemeriksaan syarat formil praperadilan dalam sistem hukum perdata Indonesia adalah untuk mengatasi permasalahan tingginya volume perkara yang menyebabkan banyak pengadilan menolak gugatan. Keterlambatan dalam mendapatkan keadilan ini disebabkan oleh proses pengadilan yang kaku dan prosedur yang ketinggalan jaman. Pemeriksaan praperadilan membantu meminimalkan penolakan dan membuat sistem hukum lebih efisien. Oleh karena itu, diperlukan aturan yang jelas untuk memastikan pemeriksaan ini merupakan bagian dari acara hukum perdata, baik melalui peraturan Mahkamah Agung maupun peraturan perundang-undangan.